Range of serum transthyretin levels in hemodialysis patients at a high risk of 1‐year mortality: A retrospective cohort study. Issue 4 (8th December 2021) - Kumagai, Etsuko; Hosohata, Keiko; Furumachi, Kazuhiro; Takai, Shinji
Abstract: Introduction: Transthyretin (TTR) is a sensitive marker of nutritional status and independent risk factor for mortality in hemodialysis patients. However, its range associated with prognosis in Japanese hemodialysis patients is unknown. Methods: Maintenance hemodialysis Patients ( n  = 664) were enrolled, and their TTR levels were measured to assess 1‐year mortality. Patients were assigned to four groups based on TTR levels: <20, 20 to <30 (control), 30 to <40, and ≥40 mg/dl. One‐year mortality at each TTR range was analyzed using a Cox proportional hazards model after adjustment for prognostic factors. Results: Seventy‐seven (11.6%) deaths were recorded during follow‐up. The hazard ratio (HR) of TTR <20 mg/dl was significantly higher compared with the control group in terms of all‐causes (HR: 3.14) and non‐cardiovascular mortality (HR: 6.986). Conclusion: TTR levels were independent and sensitive predictors of mortality in hemodialysis patients. TTR <20 mg/dl is a risk factor for 1‐year mortality in Japanese hemodialysis patients.